Avaliação clínica e laboratorial de equídeos sororreagentes para Anaplasma phagocytophilum (Rickettsiales: Anaplasmataceae) em Minas Gerais, Brasil - Luan Gaviao Prado (2014)
Equine Granulocytic Anaplasmosis is caused by Gram-positive, obligatory intracellular bacteria, member of the Anaplasmataceae family, included in the Rickettsiales order. Little is known about, disease transmission dynamics, strain and prevalence of the disease in the state of Minas Gerais. This study aimed to define seroprevalence of EGA in three localities in the state of Minas Gerais and realize a hematological and serum biochemistry evaluation of serology positive horses. 224 animal from Belo Horizonte and 172 animal from Ataléia e São Vicente de Minas were studied. In Belo Horizonte, the seroprevalence for indirect immunofluorescence assay was 53.54% (120/224). At examination of buffy coat smear a percentage of 3.14% (7/224) was find and only 2.67% of the animals were positive in polymerase chain reaction. In Ataléia and São Vicente de Minas the prevalence found in indirect immunofluorescence was 76.16% (131/172). At buffy coat smear evaluation, 12.87% (22/171) of the animals were positive and only 1.68% was positive in polymerase chain reaction. Animals from Belo Horizonte presented with hematology values within the expected for the specie. Although, values of MCHC was elevated. These animals also had neutrophils:limphocytes ratio and band cells values above of reference values. At biochemistry, only GGT was elevated. Animals that reacted in IFA from Ataléia had erythrocytes values higher than São Vicente de Minas animals. Also, it was observed thet leucocytes and lymphocytes numbers were higher than the other three groups. GGT was elevated in all animals from these groups. The results emphasize the importance of further studies on the epidemiology of this disease throughout the Brazilian territory so that control measures can be taken against the spread of the disease.